Quantum platform storage analysis: SRAM measurement block design - Xu, Boshen (Nanyang Technological University, 2023)
Cryogenic electronics have received a lot of attention in recent years as an interface solution for reading/writing quantum platforms. In cryogenic environments, semiconductor devices, such as MOSFETs, are often prone to behaving differently than at room temperature circuits. However, today's cryogenic MOSFET models for simulation software are not accurate, which becomes the main concern when designing quantum control systems. Storage circuits suffer from this effect, requiring a measurement block for the SRAM architecture operation under extremely short operation cycles that match the fast operation of quantum processors. In this paper, a measurement block for such operations with extremely short pulses is implemented, and some detailed design strategies are discussed. In terms of simulation results, logical analysis was conducted to determine the effects temperature has on the integrated circuit. After simulations for both pre-layout and post-layout, a pulse generator with a 200ps minimum, 5ns maximum, and 15ps step was achieved and verified.